Perlindungan Hukum Terhadap Bank Pembayar Talangan Haji - Muhammad, Ilyas; Winarno, Bambang; Safaat, Rachmad (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study discusses legal protection for banks with the status of BPS BPIH in curbing haj bailout financing that has passed the provisions of the Indonesian Ministry of Religion, in Article 12A paragraph (3) of the Regulation of the Minister of Religion Number 24 of 2016 which formulates “In the event that there are still haj bailout funds has not been resolved after the deadline as referred to in paragraph (2) the portion number for Pilgrims is still active ”. This study uses a normative juridical method with a statutory approach and a conceptual approach. The result is legal protection for BPS BPIH in obtaining its right to obtain certainty of repayment of funds for financing the status of the portion of the hajj is still active as regulated in Article 12A paragraph (3) of the Regulation of the Minister of Religion Number 24 of 2016. The formulation of the settlement of haj bailout financing through the fulfillment of formal requirements the formation of legislation by involving the financial services authority in the company, and the material requirements, namely by accommodating the rights of all stakeholders of haj bailout financing.